2015
DOI: 10.1371/journal.pone.0141967
|View full text |Cite|
|
Sign up to set email alerts
|

Differential microRNA Expression in Fast- and Slow-Twitch Skeletal Muscle of Piaractus mesopotamicus during Growth

Abstract: Pacu (Piaractus mesopotamicus) is a Brazilian fish with a high economic value in pisciculture due to its rusticity and fast growth. Postnatal growth of skeletal muscle in fish occurs by hyperplasia and/or hypertrophy, processes that are dependent on the proliferation and differentiation of myoblasts. A class of small noncoding RNAs, known as microRNAs (miRNAs), represses the expression of target mRNAs, and many studies have demonstrated that miR-1, miR-133, miR-206 and miR-499 regulate different processes in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 41 publications
5
27
0
Order By: Relevance
“…Chu et al [84]described, in juvenile Siniperca chuatsi , that several miRNAs highly expressed in fast muscle had lower expression in slow muscle and that miRNAs highly expressed in slow muscle had lower expression in fast muscle. This finding was also observed in our laboratory, where a difference in miRNA expression between fast and slow muscles in pacus during development was described [85]. Similar results were found in the present experiment, where we observed an increase in miR-1 and miR-206 expression in fast muscle and a decrease of miR-206 in slow muscle after refeeding, also described by Wiberg et al [86] in the soleus and gastrocnemius of mice subjected to denervation.…”
Section: Discussionsupporting
confidence: 93%
“…Chu et al [84]described, in juvenile Siniperca chuatsi , that several miRNAs highly expressed in fast muscle had lower expression in slow muscle and that miRNAs highly expressed in slow muscle had lower expression in fast muscle. This finding was also observed in our laboratory, where a difference in miRNA expression between fast and slow muscles in pacus during development was described [85]. Similar results were found in the present experiment, where we observed an increase in miR-1 and miR-206 expression in fast muscle and a decrease of miR-206 in slow muscle after refeeding, also described by Wiberg et al [86] in the soleus and gastrocnemius of mice subjected to denervation.…”
Section: Discussionsupporting
confidence: 93%
“…The pacu ( Piaractus mesopotamicus ), which is characterized by hardiness, fast growth, adaptation to artificial feeding and flavorsome meat (Castagnolli and Cyrino, 1986 ), is a valuable resource in Brazilian aquaculture (Urbinati and Gonçalves, 2005 ). Duran et al ( 2015 ) and Paula et al ( 2017 ) studied the role of skeletal muscle miRNAs in this Neotropical fish during development and under food restriction, respectively. Duran et al ( 2015 ) analyzed the impact of the miRNA-target interactions of miR-1/ hdac4 , miR-133-a/b/ srf , miR-206/ pax7 , and miR-499/ sox6 in fast- and slow-twitch skeletal muscles during growth.…”
Section: A Review Of Mirnas In Farmed Fishesmentioning
confidence: 99%
“…In tilapia (Oreochromis niloticus), it has been shown that miR-206 regulates muscle growth by targeting the 3′-UTR of IGF-1 transcript (Yan et al, 2013). In Paralichthys olivacues, it has been shown that miR-133a targets SRF mRNA (Duran et al, 2015;Su et al, 2015) as in mammals. Recently, we published a miRNA repertoire of a wide variety of tissue that identifies some muscle-specific miRNAs (Juanchich et al, 2016).…”
Section: Introductionmentioning
confidence: 99%